Vehicle stability enhancement based on second order sliding mode control - Hamzah, N. (2013)
The vehicle handling and stability in emergency situation can be enhanced with direct yaw moment control (DYC). In this paper, a new controller using super twisting technique based on second order sliding mode control (SOSM) is proposed for the yaw moment control. The controller is designed based on two degree of freedom (2DOF) nonlinear model. The effectiveness of the proposed controller is compared to PI controller and conventional sliding mode controller by co-simulations in CarSim and Matlab/Simulink. The results show that the SOSM give better performance in tracking the desired response necessary for the vehicle handling and stability. In addition, the chattering phenomenon is also reduced, giving a smooth tracking trajectory.